2017
DOI: 10.1080/20423489.2017.1408177
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of broadleaved woodland under the 1985 Broadleaves Policy stimulates ground flora recovery at Shabbington Woods, southern England

Abstract: Forestry policy and practice changes during the 20 th Century led to major effects on the composition and structure of Shabbington Woods, southern England. Coppice-withstandards stands were clear-felled during the Second World War and replanted with conifer/conifer-broadleaved mixtures in which the conifer was dominant. Since 1985 broadleaves have been favoured. In 1983 the ground flora had been recorded in six plantation stands of different tree species and compared with three remnant broadleaved stands. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It has been shown that traditional management techniques such as coppicing significantly increase the abundance and richness of woodland plant species in the understory (Barkham, 1992; Fuller & Warren, 1993; Kirby et al, 2017). Some of the woodlands of this study are too young to be coppiced, however, thinning to counteract the overshading of Salix viminalis could increase the biodiversity of ground flora by allowing a more diverse range of plants to compete with the ivy (Kirby & Thomas, 2017). The dominance of plants such as ivy, or the presence of trees which block out light may be a good milestone to assess this by.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that traditional management techniques such as coppicing significantly increase the abundance and richness of woodland plant species in the understory (Barkham, 1992; Fuller & Warren, 1993; Kirby et al, 2017). Some of the woodlands of this study are too young to be coppiced, however, thinning to counteract the overshading of Salix viminalis could increase the biodiversity of ground flora by allowing a more diverse range of plants to compete with the ivy (Kirby & Thomas, 2017). The dominance of plants such as ivy, or the presence of trees which block out light may be a good milestone to assess this by.…”
Section: Discussionmentioning
confidence: 99%
“…World War II, caused another devastating loss of standing timber, the brunt of which was carried by the former royal forests and privately owned forests, as most of the newly planted state owned conifer plantations were still too young to be of much use (Foot 2010). In Shabbington Woods in southern England, for instance, a remnant of the former royal forest of Bernwood, traditional broadleaved coppicewith-standards tree stands were clear-felled during the War and later replanted with mono-culture conifer or conifer-broadleaved mixtures in which the conifer was dominant (Kirby and Thomas 2017). The sudden visual effects of tree felling in many parts of the country were considerable (Foot 2010).…”
Section: Land-use and Landscape Change Due To Afforestationmentioning
confidence: 99%